Ecological and Taxonomical Perspective of Yeasts in Indonesia - WELLYZAR SJAMSURIDZAL; ARIYANTI OETARI; ATIT KANTI; RASTI SARASWATI; CHIHARU NAKASHIMA; YANTYATI WIDYASTUTI; ANDO KATSUHIKO (Indonesian Society for microbiology, 2010)
In the course of ecological and taxonomical study of yeasts in Indonesia, a total of 2147 yeast isolates from 315 samples in the year 2003, 2005, 2006, and 2008 had been obtained from eight locations e.g. Liwa (Sumatera), Cibinong (Java), Cibodas (Java), Kutai (Kalimantan), Enrekang (Sulawesi), Pucak (Sulawesi), Gili and Kuta (Lombok), and Kupang (Timor). Leaves, flowers, litters, soils, epiphytic soils, insects and insect's nests were collected for yeasts isolation. Our molecular identification based on D1/D2 region of nuclear large-subunit rDNA and the internal transcribed spacer (ITS) regions sequence data on 525 representative isolates revealed that 306 isolates belong to 48 described species (18 genera) and 209 strains belong to 19 undescribed species (19 genera), and 10 isolates were discarded because of contamination. Based on their substrates, litter had the highest yeasts genera (19) followed by soils (18), flowers (10), leaves (6), epiphytic soils (4), and insects and insect's nests (4). Genera found on soils were also common on litters. Yeasts genera found on flowers and epiphytic soils were common on leaves and litters. The genera Aureobasidium, Cryptococcus, Pseudozyma, Rhodotorula and Sporidiobolus were found in all substrates. Based on their locations, Kutai had the highest number of genera (15) followed by Cibodas (10), Cibinong (10), Enrekang (10), Kupang (10), Pucak (9), Liwa (7), and Lombok (7). The genus Cryptococcus was found in all locations. Our study shed a light to detection of many new taxa of yeasts, 41% of yeasts found in this study represented novel taxa.